2017
DOI: 10.1080/03630269.2017.1374969
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban Use in Patients with Hemoglobinopathies

Abstract: The use of rivaroxaban in patients with hemoglobinopathies and thrombotic events has not been studied extensively. Here we present eight cases of such patients, five receiving rivaroxaban for stroke and systemic embolism prevention due to non-valvular atrial fibrillation and three for deep vein thrombosis treatment. The follow-up period ranged from 6 to 34 months. During this period none of the patients experienced any thrombotic or bleeding event.There were no other adverse events reported. Further studies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Only one study tested the effectiveness of rivaroxaban in a very small group of patients with β-thalassemia and AF. In five patients, the direct inhibitor of factor X was administered, while in three patients, warfarin was prescribed; during the follow-up none of the eight patients suffered from any event of either ischemic or hemorrhagic type [ 60 ]. Further data are therefore necessary in order to assess the non-inferiority of DOACs respect to vitamin K inhibitors in patients with hemoglobinopathies.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Only one study tested the effectiveness of rivaroxaban in a very small group of patients with β-thalassemia and AF. In five patients, the direct inhibitor of factor X was administered, while in three patients, warfarin was prescribed; during the follow-up none of the eight patients suffered from any event of either ischemic or hemorrhagic type [ 60 ]. Further data are therefore necessary in order to assess the non-inferiority of DOACs respect to vitamin K inhibitors in patients with hemoglobinopathies.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Warfarin is the most used anticoagulant. Only one study explored the effectiveness of the new oral anticoagulant rivaroxaban in a small group of patients with β-TM and AF, and none of the patients experienced any thrombotic or bleeding event during follow-up [36]. Again, drug interactions should be carefully taken into consideration.…”
mentioning
confidence: 99%
“…The reason for this is uncertain as the subjects appeared to be adherent to study drug based on pill count. While there are no large controlled studies of direct oral anticoagulants (DOACs) in SCD patients with venous thromboembolism, small cohort studies suggest that these agents are efficacious at approved doses 9,10 . In laser Doppler velocimetry studies, no significant improvements were observed in the measures of microvascular flow, TH1 and AH/AO, following treatment with rivaroxaban.…”
Section: Discussionmentioning
confidence: 99%